2017
DOI: 10.1038/nmicrobiol.2016.263
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional dissemination and evolution of Burkholderia pseudomallei

Abstract: *Correspondence should be addressed to Claire Chewapreecha (cchewapreecha@gmail.com) and Sharon Peacock (sharon.peacock@lshtm.ac.uk). § Deceased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
161
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(190 citation statements)
references
References 54 publications
13
161
0
5
Order By: Relevance
“…Analysis of SNPs in whole-genome sequences appears quite promising as a way to correlate isolates with geographic origin ( 4 , 10 , 11 ). The ability to link a strain with a geographic origin has been shown to be increasingly useful, especially in areas such as the US mainland, which so far does not appear to be endemic for melioidosis ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of SNPs in whole-genome sequences appears quite promising as a way to correlate isolates with geographic origin ( 4 , 10 , 11 ). The ability to link a strain with a geographic origin has been shown to be increasingly useful, especially in areas such as the US mainland, which so far does not appear to be endemic for melioidosis ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies by Sarovich et al ( 10 ) and Chewapreecha et al ( 11 ) added support to this hypothesis by inferring relatedness from whole-genome SNPs. These studies indicate that Southeast Asia was the source of isolates from Africa, and Africa then became the source for B. pseudomallei in the Western Hemisphere, potentially associated with transfer to the Americas by the slave trade ( 10 , 11 ).…”
mentioning
confidence: 98%
“…A subsequent study evaluating the dissemination and evolution of B. pseudomallei has identified distinct evolutionary bacterial lineages after sequencing and comparing more than 250 B. pseudomallei strains isolated between 1935 and 2013 from humans with melioidosis or environmental samples, and representing countries across Australia, Asia, Africa and Central and South America [17]. This genomic global analysis confirmed that the Australian continent represents an early reservoir for B. pseudomallei , with the bacteria being first transmitted to southeast Asia with subsequent dissemination to South and East Asia [17]. Further, the study also confirmed that B. pseudomallei isolates from African origin were transmitted to Central and South America between 1650 and 1850, which correspond to the period representing the slave trade.…”
Section: Predicted and Evidenced Global Incidence Of Diseasementioning
confidence: 99%
“…The transmission dynamics of a Burkholderia dolosa 523 CF outbreak was tracked in 14 patients over 16 years and identified mutations in the 112 524 isolates that showed parallel evolution towards increased antibiotic resistance and tolerance 525 of low oxygen (Lieberman et al 2011). The cause of melioidosis, Burkholderia pseudomallei, 526 has been subjected to arguably the most extensive genomic characterisation because of its 527 pathogenicity and due to its threat as a bioterrorism agent (Chewapreecha et al 2017). The presence of subinhibitory concentrations of trimethoprim (1 µg/ml) reduced the production of bongkrekic acid in strain BCC1678 as shown the HPLC metabolite analysis comparing production levels against the control condition without antibiotic.…”
mentioning
confidence: 99%
“…Genome sequencing of 469 B. pseudomallei isolates showed the species comprised two 529 distinct populations, an ancestral Australian reservoir that anthropogenically transmitted and 530 diverged within Asia, and spread further via the slave trade from Africa to South America 531(Chewapreecha et al 2017). Mapping the phylogenomics of B. ambifaria as a historically used 532 biopesticide revealed the BGC for cepacin A, a key antimicrobial mediating plant protection 533 against pathogenic oomycetes(Mullins et al 2019).…”
mentioning
confidence: 99%